Rumba under Fire: The Arts of Survival from West Point to Delhi - Dumitrescu, Irina (punctum books, 2016)
A professor of poetry uses a deck of playing cards to measure the time until her lover returns from Afghanistan. Congolese soldiers find their loneliness reflected in the lyrics of rumba songs. Survivors of the siege of Sarajevo discuss which book they would have never burned for fuel. A Romanian political prisoner writes her memoir in her head, a book no one will ever read. These are the arts of survival in times of crisis. Rumba Under Fire proposes we think differently about what it means for the arts and liberal arts to be "in crisis." In prose and poetry, the contributors to Rumba Under Fire explore what it means to do art in hard times. How do people teach, create, study, and rehearse in situations of political crisis? Can art and intellectual work really function as resistance to power? What relationship do scholars, journalists, or even memoirists have to the crises they describe and explain? How do works created in crisis, especially at the extremes of human endurance, fit into our theories of knowledge and creativity?